PENGENALAN NAMA-NAMA 25 NABI DAN RASUL BERBASIS MEDIA FLASHCARD DI TPA AL-FIRDAUS - Mazrur, Mazrur; Surawan, Surawan; Norhidayani, Norhidayani; Nurrahmi, Dwi (Mafaza : Jurnal Pengabdian Masyarakat, 2025)
Early childhood religious education is very important in shaping children's religious character from an early age, because at this stage children are in a period of rapid cognitive and affective development, so it is important to instill values of faith from an early age. The objective of this service project is to introduce the names of the 25 Prophets and Messengers along with their miracles to the children of TPA Al-Firdaus Palangka Raya using flashcards, as well as to enhance the learning process through the use of innovative, effective, and age-appropriate educational media. The method used in this service project is the Service Learning (SL) method, which involves four stages: first, analysis/preparation; second, planning and program development; third, implementation; and finally, evaluation. The outcome of this community service initiative is that the children at the Al-Firdaus Palangka Raya TPA are now able to recognize and remember the names of the 25 Prophets and Messengers along with their miracles, through the symbolic images on the flashcards featuring the 25 Prophets and Messengers. This was demonstrated when the children at TPA Al-Firdaus were able to answer and guess the names of the Prophets and Messengers depicted in the flashcards simply by looking at the symbolic images provided accurately and correctly.